Active tendon control of cable stayed bridges a large scale demonstration. - Bossens, Frederic
This paper presents a strategy for active damping of cable structures, using active tendons. The first part of the paper summarizes the theoretical background : the control law is briefly presented together with the main results of an approximate linear theory which allows the prediction of closed loop poles with a root locus technique. The second part of the paper reports on experimental results obtained with two test structures : the first one is a small size mock up representative of a cable stayed bridge during the construction phase. The control of the parametric vibration of passive cables due to deck vibration is demonstrated. The second one is a 30 m long mock up built on the reaction wall of the ELSA test facility at the JRC Ispra (Italy); this test structure is used to demonstrate the practical implementation of the control strategy with hydraulic actuators.